Identification and characterization of a novel sucrose-non-fermenting protein kinase/AMP-activated protein kinase-related protein kinase, SNARK - LEFEBVRE, Diana L.; BAI, Yahong; SHAHMOLKY, Nazanin; SHARMA, Monika; POON, Raymond; DRUCKER, Daniel J.; ROSEN, Cheryl F. (Biochemical journal, 2001)
Subtraction hybridization after the exposure of keratinocytes to ultraviolet radiation identified a differentially expressed cDNA that encodes a protein of 630 amino acid residues possessing significant similarity to the catalytic domain of the sucrose-non-fermenting protein kinase (SNF1)/AMP-activated protein kinase (AMPK) family of serine/threonine protein kinases. Northern blotting and reverse-transcriptase-mediated PCR demonstrated that mRNA transcripts for the SNF1/AMPK-related kinase (SNARK) were widely expressed in rodent tissues. The SNARK gene was localized to human chromosome 1q32 by fluorescent in situ hybridization. SNARK was translated in vitro to yield a single protein band of approx. 76 kDa; Western analysis of transfected baby hamster kidney (BHK) cells detected two SNARK-immunoreactive bands of approx. 76-80 kDa. SNARK was capable of autophosphorylation in vitro; immunoprecipitated SNARK exhibited phosphotransferase activity with the synthetic peptide substrate HMRSAMSGLHLVKRR (SAMS) as a kinase substrate. SNARK activity was significantly increased by AMP and 5-amino-4-imidazolecarboxamide riboside (AICAriboside) in rat keratinocyte cells, implying that SNARK might be activated by an AMPK kinase-dependent pathway. Furthermore, glucose deprivation increased SNARK activity 3-fold in BHK fibroblasts. These findings identify SNARK as a glucose- and AICAriboside-regulated member of the AMPK-related gene family that represents a new candidate mediator of the cellular response to metabolic stress.